Heavy metal concentrations and ecological risk assessment for surface sediment of Da Qaidam Salt Lake in Qaidam Basin, northern Tibetan Plateau. Issue 1 (June 2020) - Gao, Chunliang; Yu, Junqing; Min, Xiuyun; Cheng, Aiying
Abstract: The paper focused on heavy metal (Cr, Cu, Pb, Zn, As, Co, Ni and Mn) concentrations from surface sediment in the southeastern Da Qaidam Salt Lake. Based on the pressed powder pellet method and X-ray fluorescence spectrometry analysis, as well as the enrichment factor, geoaccumulation index and potential ecological risk index, the possible sources and pollution level of heavy metals were studied. The results showed that spatial distributions of heavy metal concentration were indicative of nonuniform characteristics in different zones of Da Qaidam Salt Lake, the average enrichment level of heavy metals followed the decreasing order: EF (As) > EF (Mn) > EF (Cu) > EF (Zn) > EF (Pb) > EF (Cr) > EF (Ni) > EF (Co), and arsenic was the main heavy metal contaminant. In a word, the level of heavy metal pollution in the southeastern Da Qaidam Salt Lake was not strong, but anthropogenic emissions would become the main source of heavy metals along with the frequent and strong human activities in the surrounding region.